BEBERAPA SIFAT FISIK GUBAL ANGSANA (Pterocarpus indicus) - Belly Ireeuw; Reynold P. Kainde; Josephus I. Kalangi; Johan A. Rombang (Universitas Sam Ratulangi, 2013)
ABSTRACT This research was to study about some physical properties of angsana (Pterocarpus indicus) sapwood related in wood position to wood position in trunk (base, middle, and tip) and to environmental factors (temperature and humidity). It used a faktorial design in completely randomized block with combinations of 3 environmental condition and 3 wood position in trunk. These nine treatments are repeated three times. The results showed that moisture content, wood density, and volumetric shrinkage of angsana sapwood could be influenced by wood position in trunk (base, middle, and tip). The swelling property of angsana sapwood was not influenced by wood position in trunk but it was influenced by environmental factors. Key words : physical properties, sapwood, wood position, temperature, humidity